A new juvenile Yamaceratops (Dinosauria, Ceratopsia) from the Javkhlant Formation (Upper Cretaceous) of Mongolia - Minyoung Son; Yuong-Nam Lee; Badamkhatan Zorigt; Yoshitsugu Kobayashi; Jin-Young Park; Sungjin Lee; Su-Hwan Kim; Kang Young Lee (PeerJ, 2022)
Here we report a new articulated skeleton of Yamaceratops dorngobiensis (MPC-D 100/553) from the Khugenetjavkhlant locality at the Shine Us Khudag (Javkhlant Formation, ?Santonian-Campanian) of the eastern Gobi Desert, Mongolia, which represents the first substantially complete skeleton and the first juvenile individual of this taxon. The specimen includes a nearly complete cranium and large portions of the vertebral column and appendicular skeleton. Its skull is about 2/3 the size of the holotype specimen, based on mandibular length. Its juvenile ontogenetic stage is confirmed by multiple indicators of skeletal and morphological immaturity known in ceratopsians, such as the long-grained surface texture on the long bones, the smooth external surface on the postorbital, open neurocentral sutures of all caudal vertebrae, a large orbit relative to the postorbital and jugal, the low angle of the lacrimal ventral ramus relative to the maxillary teeth row, narrow frontal, and straight ventral edge of the dentary. Osteohistological analysis of MPC-D 100/553 recovered three lines of arrested growth, implying around 3 years of age when it died, and verified this specimen’s immature ontogenetic stage. The specimen adds a new autapomorphy of Yamaceratops, the anteroventral margin of the fungiform dorsal end of the lacrimal being excluded from the antorbital fossa. Furthermore, it shows a unique combination of diagnostic features of some other basal neoceratopsians: the ventrally hooked rostral bone as in Aquilops americanus and very tall middle caudal neural spines about or more than four times as high as the centrum as in Koreaceratops hwaseongensis, Montanoceratops cerorhynchus, and Protoceratops andrewsi. The jugal with the subtemporal ramus deeper than the suborbital ramus as in the holotype specimen is also shared with A. americanus, Liaoceratops yanzigouensis, and juvenile P. andrewsi. Adding 38 new scorings into the recent comprehensive data matrix of basal Neoceratopsia and taking into account the ontogenetically variable characters recovered Y. dorngobiensis as the sister taxon to Euceratopsia (Leptoceratopsidae plus Coronosauria). A second phylogenetic analysis with another matrix for Ceratopsia also supported this position. The new phylogenetic position of Y. dorngobiensis is important in ceratopsian evolution, as this taxon represents one of the basalmost neoceratopsians with a broad, thin frill and hyper-elongated middle caudal neural spines while still being bipedal.